2022
DOI: 10.1136/bmjopen-2022-065897
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and longevity of antibodies against SARS-CoV-2 among primary healthcare providers in Belgium: a prospective cohort study with 12 months of follow-up

Abstract: ObjectivesTo estimate the prevalence, incidence and longevity of antibodies against SARS-CoV-2 among primary healthcare providers (PHCPs).DesignProspective cohort study with 12 months of follow-up.SettingPrimary care in Belgium.ParticipantsAny general practitioner (GP) working in primary care in Belgium and any other PHCP from the same GP practice who physically manages (examines, tests, treats) patients were eligible. A convenience sample of 3648 eligible PHCPs from 2001 GP practices registered for this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…Our results suggest that PHCWs were not at higher risk of SARS-CoV-2 infection than the general adult population (19–64 years old) over the first eighteen months of the pandemic. These findings are consistent with some studies 4 , 6 , 7 but conflicting with others 5 . The discrepancies in results may be explained by the study periods.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results suggest that PHCWs were not at higher risk of SARS-CoV-2 infection than the general adult population (19–64 years old) over the first eighteen months of the pandemic. These findings are consistent with some studies 4 , 6 , 7 but conflicting with others 5 . The discrepancies in results may be explained by the study periods.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies showed substantial variability in prevalence and risk factors for SARS-CoV-2 infection among HCWs, attributed to different job roles, exposure to COVID-19 patient, access to PPE, data collection periods, and community prevalence 3 , 4 . Some studies reported a higher risk (between two- and seven-fold) of infection among HCWs from hospital or other healthcare settings than in the general population 5 , while others have not found such differences 4 , 6 , 7 . While some authors reported a dose–response association between COVID-19-patient exposure and the risk of SARS-CoV-2 infection 8 , 9 , others showed that community exposure was associated with infection but workplace factors were not 10 12 .…”
Section: Introductionmentioning
confidence: 98%
“…Of note, in our cohort study we observed an RST-based prevalence of up to 93.9% in December 2021,4 37 which is higher than what could be expected with the sensitivity and specificity of the RST estimated in this validation study. As shown in figure 2, using imperfect sensitivity and specificity estimates overestimates/underestimates true seroprevalence.…”
Section: Discussioncontrasting
confidence: 66%
“…Important strengths of our study are the clearly defined infection and vaccine status of every individual study participant and the relatively large share of previously unvaccinated participants. This enabled us to adequately disentangle the effects of viral variant and of SARS-CoV-2 vaccination on the occurrence of PASC symptoms, a task which is increasingly becoming unrealizable due to high vaccination and infection rates [ 38 ]. Probably the most important strength is the inclusion of uninfected controls using (repetitive) SARS-CoV-2 serologies.…”
Section: Discussionmentioning
confidence: 99%